Identifying Students' Learning Styles on Reading Comprehension Achievement - Handayani Setiowati (Jurnal Pedagogy, 2019)
This study aims to identify the effect of type of students’learning styles in reading comprehension achievement. The design of the research was a descriptive quantitative research that used a case study design. A total of 20 students of reading class on the second semester of IAIN Metro was sample of this research. In collecting the data, the researcher used questionnaire of learning style and reading comprehension test. In the analysis of data, the writer classified the categorization of learning style from the questionnaire and the scores of reading comprehension tests. Then, the result was analyzed by comparing the mean score in test manually using by percentage correct. The finding of the research the students have three types of learning style, they are visual (45%), auditory (30%), and kinesthetic (25%), in which visual is the most dominant. whereas the result of reading comprehension test, the mean score of visual is 79.2, auditory is 70.8, and kinesthetic is 65. In conclusion, It showed that the students of reading class on second semester of IAIN Metro used three types of learning style, but visual learning style is the most dominant learning style the students have.